2019
DOI: 10.3389/fphy.2019.00123
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Processes in Complex Media: New Vistas on Anomalous Diffusion

Abstract: Normal or Brownian diffusion is historically identified by the linear growth in time of the variance and by a Gaussian shape of the displacement distribution. Processes departing from the at least one of the above conditions defines anomalous diffusion, thus a nonlinear growth in time of the variance and/or a non-Gaussian displacement distribution. Motivated by the idea that anomalous diffusion emerges from standard diffusion when it occurs in a complex medium, we discuss a number of anomalous diffusion models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In soft condensed matter, the length scale (l D ) by which we can probe media structure is approximately equal to the square root of the mean-square displacement (MSD) of the diffusing particles: l D ≈ MSD 1/2 . In the normal Brownian diffusion approximation, the MSD of diffusing water molecules is linearly proportional to the diffusion coefficient D and the time t during which the diffusion process is observed (MSD ∝ D · t) [ 13 ]. Taking typical values for free water diffusion and diffusion time achievable on NMR scanners (e.g., D ≈ 3 μm 2 /ms and t ≈ 10–100 ms), molecular displacements occur over linear distances of about 10–40 micrometers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In soft condensed matter, the length scale (l D ) by which we can probe media structure is approximately equal to the square root of the mean-square displacement (MSD) of the diffusing particles: l D ≈ MSD 1/2 . In the normal Brownian diffusion approximation, the MSD of diffusing water molecules is linearly proportional to the diffusion coefficient D and the time t during which the diffusion process is observed (MSD ∝ D · t) [ 13 ]. Taking typical values for free water diffusion and diffusion time achievable on NMR scanners (e.g., D ≈ 3 μm 2 /ms and t ≈ 10–100 ms), molecular displacements occur over linear distances of about 10–40 micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is recognized that anomalous subdiffusion [ 13 ] exists in complex and highly heterogeneous media, such as biological tissues [ 31 ] and biomaterials [ 32 , 33 ]. Therefore, anomalous subdiffusion is a probe of submicroscopic organization, as shown in theoretical [ 34 ] and experimental works performed by optical microscopy [ 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal diffusion of bulk water in tissues is not capable of detecting any of the characteristics above, providing nonlocal, diffusion measurement averaged on the l D length scale. As well summarized by Di Tullio et al (2019) and introduced above, normal or Brownian diffusion is identified by the linear growth in time of the MSD and by the Gaussian shape of the molecular motion propagator. Processes departing from at least one of the above conditions define anomalous diffusion, thus a nonlinear growth in time of the MSD and/or a non-Gaussian displacement distribution.…”
Section: Introductionmentioning
confidence: 96%
“…Fractional diffusion is characterized by non-Gaussian statistics and nonlinear scaling in time of the mean-squared displacement [20][21][22]28]. Many different approaches have been implemented and extensively analyzed to reproduce this type of diffusion, see, e.g., [2,9,10]. In particular, we recall the continuous time random walk (CTRW) [11], where a power-law tailed distribution of the waiting times can be introduced to generate fractional diffusion processes.…”
Section: Introductionmentioning
confidence: 99%